SUBJEKTYVUMAS, SAVIPATIRTIS IR ANONIMIŠKUMAS. - Jonkus, Dalius (Problems / Problemos, 2013)
This article investigates the problem of egological consciousness and its connection with self-experience. By criticizing the conception of egological consciousness Gurwitsch and Sartre demonstrate that no foreign instance is neccecary to guarantee the unity of consciousness. By using that theory they claim that the ego, as a unifying entity for consciousness, does not exist. However, the intentionality of consciousness means not only its unity or focus on wordly objects, but also its self-givenness. Consciousness realizes itself as self-consciousness not only with the help of reflection as understood in classic philosophy but also by means of direct self-experience. The model of this kind of experience, which implicates self-experience, proposed by Husserl and other phenomenologists, is actualized today in the studies of Dan Zahavi. Reflection means distance to the self, but direct self-experience is a pre-reflective cogito. The aim of this artice is to reveal the connection between intentionality and egological self-experience, between selfgivenness of consciousness and a first-person perspective. The subconsciousness is insufficient as a consciousness determinating basis, because it supposes an outer connection of consciousness with subconsciousness. The consciousness should be understood not as a finished object, but as an intention to become conscious.